The Impact of Service Excellence on Customer Satisfaction in Tax Service Offices: A Systematic Literature Review - Hardini, Resti; Digdowiseiso, Kumba (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The principle of customer satisfaction becomes very relevant in tax agencies, where good service can create a positive experience for taxpayers. This research aims to determine how the implementation of Service Excellence at the Tax Service Office influences customer perception and satisfaction and to choose the positive impact of Service Excellence on interactions between tax officers and taxpayers on the level of customer satisfaction at the Tax Service Office. The structure of this research literature review reflects the systematic approach applied in conducting a literature review to support understanding the impact of Service Excellence on customer satisfaction at the Tax Service Office. This research shows that implementing Service Excellence at the Tax Service Office provides better service and creates better relationships between tax institutions and taxpayers. If applied consistently, these principles can sustainably impact customer satisfaction, taxpayer compliance, and the image of tax institutions in society.